The Use of Interactive Teaching Aids by Special Education Teachers in Teaching Science to Students With Autism Spectrum Disorder (ASD) - Samatova, Aziza; Amalina Rusli, Nor (Central European Journal of Educational Research, 2025)
This study explores the use of interactive teaching aids by special education teachers in teaching science to students with autism spectrum disorder (ASD). It identifies effective tools, challenges educators face, and strategies for optimizing their use. Research questions focus on commonly used aids and barriers to implementation, given the need for inclusive and tailored educational approaches. Existing literature underscores the benefits of interactive teaching aids for students with ASD, particularly digital tools like interactive whiteboards, tablets, and digital storytelling. These resources enhance engagement, support visual and kinesthetic learning, and improve social interaction skills. However, challenges persist, including insufficient teacher training, limited access to technology, and the need for individualized adaptations. A qualitative methodology was employed, involving semi-structured interviews with 10 special education teachers. Thematic analysis using NVivo software provided insights into teacher experiences. Findings indicate that interactive teaching aids improve engagement and comprehension but are hindered by resource constraints, technical issues, and variability in student attention. Despite widespread recognition of their benefits, research on the specific application of interactive teaching aids in ASD science education remains limited. The long-term impact on learning retention and tool adaptability across contexts also requires further investigation. This study concludes that interactive teaching aids significantly enhance science education for students with ASD. Addressing barriers through targeted training, better resource allocation, and regular maintenance is crucial. Future research should explore long-term effects and optimize strategies for integrating these tools in diverse educational settings.